Transcriptomics in brown algae - Heinrich, Sandra (My University, 2015)
Brown algae are distributed worldwide on rocky shores. They are importenet components of ecosystems, they provide habitat, shelter and serve as nurseries for various marine organisms. The geographic as well as depth distribution of macroalgae is constrained by abiotic factors, especially light and temperature. It is therefore likely that due to the global change, distribution patterns of these organisms will change. In this work the molecular acclimation of two prominent brown macroalgae, Saccharina latissima (Arctic) and Desmarestia anceps (Antarctic), was analyzed and the acclimation potential of both species was compared.
Keywords: Feofíceas; Transcriptomics; Brown algae